Reliability, criterion-concurrent validity, and construct-discriminant validity of a head-marking version of the taekwondo anaerobic intermittent kick test - Tayech, A.; Arbi Mejri, M.; Makhlouf, I.; Uthof, A.; Hambli, M.; Behm, D. G.; Chaouachi, A. (Biology of Sport, 2022)
This study aimed to examine the reliability and validity of a head-marking version of the taekwondo anaerobic intermittent kick test (TAIKT-head). Twenty-seven (21 males and 6 females) taekwondo athletes performed TAIKT-head on two occasions (test-retest). In addition, they performed the chest-marking version of the TAIKT (TAIKT-chest), 30-s continuous jump (CJ30s), countermovement jump (CMJ) and flexibility tests. To establish TAIKT-head`s construct validity (discriminatory capability), two subgroups were identified based on their international and national taekwondo results: 15 elite (12 males and 3 females) and 12 sub-elite (9 males and 3 females) athletes. TAIKT-head showed high relative (ICCs = 0.90) and absolute (SEMs < SWCs) reliability. The comparison between TAIKT-head and TAIKT-chest revealed that absolute and relative peak and mean powers were higher (p < 0.001) in TAIKT-head than in TAIKT-chest. In contrast, the fatigue index and rating of perceived exertion were lower in TAIKT-head than in TAIKT-chest (p < 0.001 and p < 0.01, respectively), with no significant difference between the two tests regarding physiological variables. Significant correlations between TAIKT-head and TAIKT-chest (r ranged from 0.74 to 0.53), CJ30s (r ranged from 0.84 to 0.43), and CMJ (r ranged from 0.88 to 0.79) were mostly "very large". There was no association between TAIKT-head and flexibility tests. Elite athletes showed greater TAIKT-head performances than sub-elite counterparts. Receiving operating characteristic analysis indicated that the TAIKT-head effectively discriminated between elite and subelite athletes. In conclusion, the TAIKT-head is a reliable and valid test to evaluate the specific intermittent anaerobic power of taekwondo athletes through the most used kicking technique at the head level.